Margin status in vulvovaginal melanoma: Management and oncologic outcomes of 50 cases - Alli M. Straubhar; May P. Chan; Shitanshu Uppal (Elsevier, 2023)
Objectives: To determine the influence of margin status, including preinvasive disease at the margin, on local recurrence and overall survival (OS) in patients with vulvovaginal melanoma. Methods: All patients with Stage 0-III vulvovaginal melanoma treated with primary surgical management between 1/2010-12/2019 were included. Margin status was categorized as negative, preinvasive disease (atypical junctional melanocytic hyperplasia and melanoma in situ), and invasive melanoma. Kaplan-Meier analyses were performed for local progression free survival (PFS) and OS. The impact of clinical and pathologic factors on local PFS and OS were assessed with Cox-regression analyses. Results: Fifty patients with a median follow-up of 48 months (range 3-119) were included. The median age was 63 years (range 20-83). Twenty percent (N = 10) had Stage 0 disease, 18% (N = 9) had Stage I, 46% (N = 23) had Stage II, and 16% (N = 8) had Stage III. Forty-four percent (N = 22) of patients had negative surgical margins, 46% (N = 23) had preinvasive disease at the margins, and 10% (N = 5) had invasive melanoma at the margins. The 5-year local PFS was 63% (95% CI: 42-78%) and OS was 60% (95% CI: 42-74%). Age, Breslow depth, stage, margin status, and re-resection did not significantly impact local PFS. In patients with preinvasive disease at the margin, all who recurred locally had Stage I-II disease. Conclusion: Preinvasive disease at the surgical margins may play an important role in local recurrence in patients with Stage I-II vulvovaginal melanoma. Patients with early (Stage 0) and advanced (Stage III) disease rarely recur locally and may not benefit from re-resection.